Topiramate and cognitive function: review - Santos, Karllus Andhre Leite de Mendonça (2015)
Despite the therapeutic efficacy, in its various indications, cognitive side effects are common findings with topiramate. Descriptive studies indicate nonspecific complaints cognitive, psychomotor slowness and language difficulties, as main complaints among patients who had to discontinue use of the medication, even when it shows efficacy in symptomatic control of the patient. Even in patients who do not have cognitive complaints topiramate-related, changes were found in the performance of psychometric tests. The negative cognitive effects induced by topiramate are often temporary and cease after its discontinuation. There appears to be certain conditions associated with an increased risk for the development of side effects such as titration scheme, the dose used, maintenance time polytherapy and individual susceptibility. The mechanism in which topiramate leads to cognitive impairments is still poorly understood. Neurophysiology and functional neuroimaging studies seeking to elucidate the question. The magnitude of the cognitive changes may be enough to interfere with school performance, work and social relationships and are among the leading causes of discontinuation of medication during treatment.